The Analysis of Indonesian-English Code Mixings Used in the Advertisements of Guntur Radio FM Station Bali - Jaya, Putu Wira; I Wayan Suarnajaya; Mahendrayana, Gede (International Journal of Language and Literature, 2023)
Advertisements in radio are heard by many people in promote services or products. The advertisements in the radio tend to mix the language from Indonesian to English. This study aimed to analyze the types and the functions of code mixing used in commercial and non-commercial advertisements of Guntur Radio FM Station Bali. This study was embedded research design. The research instruments used were smartphone, observation sheet, field note, transcription sheet, and classification sheet. The result of this study is shown that there were 8 types and 6 functions of code mixings in commercial advertisements. The types were insertion of word, insertion of phrase, involving changes of pronunciation, letter of the alphabet, insertion of clause, proper words, incomplete sentence, and short forms type. While, the functions were quotation, repetition, facility of expression, interjection, personalization and objectification, and qualifying message. In addition, there were 3 types and 3 functions of code mixings in non-commercial advertisements, and the types were insertion of word, insertion of clause, and incomplete sentence, while the functions were facility of expression, quotation, and phatic function.